How to handle arterial conduits in liver transplantation?: Evidence from the first multicenter risk analysis - Oberkofler, Christian Eugen; Raptis, Dimitri A.; DiNorcia, Joseph; Kaldas, Fady M.; Müller, Philip C.; Pita, Alejandro; Genyk, Yuri; Schlegel, Andrea; Muiesan, Paolo; Tun Abraham, Mauro E.; Dokus, Katherine; Hernandez-Alejandro, Roberto; et al. (Annals of surgery, 2021)
Objective: - The aims of the present study were to identify independent risk factors for conduit occlusion, compare outcomes of different AC placement sites, and investigate whether postoperative platelet antiaggregation is protective. - Background: - Arterial conduits (AC) in liver transplantation (LT) offer an effective rescue option when regular arterial graft revascularization is not feasible. However, the role of the conduit placement site and postoperative antiaggregation is insufficiently answered in the literature. - Study Design: - This is an international, multicenter cohort study of adult deceased donor LT requiring AC. The study included 14 LT centers and covered the period from January 2007 to December 2016. Primary endpoint was arterial occlusion/patency. Secondary endpoints included intra- and perioperative outcomes and graft and patient survival. - Results: - The cohort was composed of 565 LT. Infrarenal aortic placement was performed in 77% of ACs whereas supraceliac placement in 20%. Early occlusion (≤30 days) occurred in 8% of cases. Primary patency was equivalent for supraceliac, infrarenal, and iliac conduits. Multivariate analysis identified donor age >40 years, coronary artery bypass, and no aspirin after LT as independent risk factors for early occlusion. Postoperative antiaggregation regimen differed among centers and was given in 49% of cases. Graft survival was significantly superior for patients receiving aggregation inhibitors after LT. - Conclusion: - When AC is required for rescue graft revascularization, the conduit placement site seems to be negligible and should follow the surgeon's preference. In this high-risk group, the study supports the concept of postoperative antiaggregation in LT requiring AC.
Gesehen am 02.02.2022